Procedurally justifiable strategies: Integrating context effects into multistage decision making - Fynn Kemper; Philipp C. Wichardt (Kiel Institute for the World Economy (IfW), 2021)
This paper proposes a simple framework to model contextual influences on procedural decision making. In terms of utility, we differentiate between monetary payoffs and contextual psychological ones, e.g. deriving from the subjects' normative frame of reference. Monetary payoffs are treated as common knowledge while psychological payoffs are treated as partly unforeseeable. Regarding behaviour, we assume that players act optimal given their local perception of the game. As perceptions may be incorrect, we do not consider common equilibrium conditions but instead require strategies to be procedurally justifiable. As we will argue, various common inconsistencies considered in behavioural economics can be understood as procedurally justifiable behaviour. With the present framework, we add an abstract tool to the discussion which allows to consider also the behavioural implications of players foreseeing the corresponding behavioural effects̶ which is often not considered in the respective original models.
Keywords: C70; D01; D91; 330; behavioural inconsistencies; context effects; limited foresight; procedural decision making; utility